2007
DOI: 10.1111/j.1445-5994.2007.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary pericardial mesothelioma: a rare cardiac malignancy

Abstract: Figure 1 Two views of computed tomography scan of (a) the chest and (b) showing large pericardial effusion with cystic tumour (arrows) compressing the right atrium with infiltration of the mediastinum and small right-sided pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…After this no extent review has been made. Our review includes 29 cases in English literature from 1993 through 2008 where the diagnosis of primary pericardial mesothelioma was established [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. It also includes the findings from our patient and the review, presented in table 1 and table 2.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After this no extent review has been made. Our review includes 29 cases in English literature from 1993 through 2008 where the diagnosis of primary pericardial mesothelioma was established [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. It also includes the findings from our patient and the review, presented in table 1 and table 2.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Three cases with known exposure to asbestos are reported [5,6,7]. For 11 of the patients no known exposure to asbestos is reported [8,9,10,11,12,13,14,15,16]. Most of the reviewed articles do not contain any information about asbestos exposure.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Primary malignant pericardial mesothelioma accounts for 2-3% of all primary cardiac tumors and less than 1% of all mesotheliomas [2]. However, about 50% of primary pericardial tumors are mesotheliomas [3].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, platinum based couplets have been reported to provide better response rates and survival benefit. Pemetrexed in combination with platinum drugs is the standard of care in malignant mesothelioma [2], though raltitrexed as well as gemcitabine have also been shown to be effective. Here we report a patient with malignant mesothelioma of the pericardium who presented with severe dyspnea and pericardial effusion and survived only 2 months despite aggressive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to pleural mesothelioma, the association of asbestos exposure with pericardial mesothelioma is unclear (Eren and Akar, 2002; Val-Bernal et al, 2002; Lagrotteria et al, 2005; Papi et al, 2005; Luk et al, 2008). Although a few reported cases have occurred in individuals with occupational asbestos exposure (Kahn et al, 1980; Beck et al, 1982; Thomason et al, 1994; Fujiwara et al, 2005), it appears that the vast majority of recently reported cases had no known asbestos exposure (Quinn et al, 2000; Hirano et al, 2002; Reis-Filho et al, 2002; Val-Bernal et al, 2002; Susman et al, 2004; Yakirevich et al, 2004; Erdogan et al, 2005; Lagrotteria et al, 2005; Maruyama et al, 2006; Molina Garrido et al, 2006; Doval et al, 2007; Vornicu et al, 2007; Akamoto et al, 2008; Santos et al, 2008), and many were reported in younger individuals (e.g., age 19–50 years). Malignant mesothelioma of the pleural cavity was also reported to occur in a 15-year old boy with rheumatic heart disease and a prosthetic aortic valve implant; this child was reported to have no history of asbestos or chemical exposure (Tewari et al, 1989).…”
Section: Basis For Genetic Testing Of Mesothelioma and Histologicallymentioning
confidence: 99%